Dynamic Changes of the Fungal Microbiome in Alcohol Use Disorder - Hartmann, Phillipp; Lang, Sonja; Zeng, Suling; Duan, Yi; Zhang, Xinlian; Wang, Yanhan; Bondareva, Marina; Kruglov, Andrey; Fouts, Derrick E.; Stärkel, Peter; Schnabl, Bernd (Frontiers in Physiology, 2021)
Background: Alcohol-associated liver disease (ALD) is an important cause of morbidity and mortality worldwide. The intestinal microbiota is involved in the development and progression of ALD; however, little is known about commensal fungi therein. Methods: We studied the dynamic changes of the intestinal fungal microbiome, or mycobiome, in 66 patients with alcohol use disorder (AUD) and after 2 weeks of alcohol abstinence using internal transcribed spacer 2 (ITS2) amplicon sequencing of fecal samples. Results: Patients with AUD had significantly increased abundance of the genera Candida, Debaryomyces, Pichia, Kluyveromyces, and Issatchenkia, and of the species Candida albicans and Candida zeylanoides compared with control subjects. Significantly improved liver health markers caspase-cleaved and intact cytokeratin 18 (CK18-M65) levels and controlled attenuation parameter (CAP) in AUD patients after 2 weeks of alcohol abstinence were associated with significantly lower abundance of the genera Candida, Malassezia, Pichia, Kluyveromyces, Issatchenkia, and the species Candida albicans and Candida zeylanoides. This was mirrored by significantly higher specific anti-Candida albicans immunoglobulin G (IgG) and M (IgM) serum levels in AUD patients in relation to control participants, and significantly decreased anti-Candida albicans IgG levels in AUD subjects after 2 weeks of abstinence. The intestinal abundance of the genus Malassezia was significantly higher in AUD subjects with progressive liver disease compared with non-progressive liver disease. Conclusions: In conclusion, improved liver health in AUD patients after alcohol abstinence was associated with lower intestinal abundances of Candida and Malassezia, and lower serum anti-Candida albicans IgG levels. Intestinal fungi might serve as a therapeutic target to improve the outcome of patients in ALD.